Analysis Of Stem Project Seminar Results On The Effectiveness Of Project-Based Learning In The Primary School Teacher Education Program At Universitas Pattimura - Siregar, Hiba; Erlin Eveline; Eka Sriwahyuni; Abdul Sofyan; Pardosi, Sri Masnita (ISER (Indonesian Science Education Research), 2025)
This study aims to analyze the results of STEM (Science, Technology, Engineering, and Mathematics) project seminars and assess the effectiveness of Project-Based Learning (PjBL) in the Primary School Teacher Education (PGSD) Program at Universitas Pattimura. The background of the research stems from the demands of the 21st-century curriculum, which emphasizes the development of critical, collaborative, creative, and communicative competencies through contextual and applicable learning. The study employs a quantitative descriptive approach with data collected through seminar observations, project documentation, and student perception questionnaires. The research participants included fourth-semester students who had participated in STEM project seminars and project supervisors. The number of students was 30 students. Data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The integration of STEM project seminars based on Project-Based Learning (PjBL) can enhance teachers’ pedagogical competence and their skills in developing learning activities aligned with the Merdeka Curriculum.  The results show that the STEM project seminars were successfully implemented, marked by active student engagement, systematic presentations, and innovative products that practically integrated STEM elements. Project-Based Learning was found effective in enhancing conceptual understanding, 21st-century skills, as well as students' motivation and self-confidence. However, in-depth mastery of STEM concepts and students’ professional readiness still require improvement through intensive guidance and training. Overall, the STEM project seminar plays a strategic role as both an evaluation medium and a reinforcement of project-based learning within teacher education. The study recommends the development of integrative STEM guidelines and a more systematic project evaluation model to support the achievement of professional competencies among PGSD students.